Could peak oxygen uptake be estimated from proposed equations based on the six-minute walk test in chronic heart failure subjects? - Ribeiro-Samora, Giane A. (Braz J Phys Ther, 2017)
OBJECTIVES: To evaluate the agreement between the measured peak oxygen uptake (VO(2)peak) and the VO(2)peak estimated by four prediction equations based on the six-minute walk test (6MWT) in chronic heart failure patients. METHOD: Thirty-six chronic heart failure patients underwent cardiopulmonary exercise testing and the 6MWT to assess their VO(2)peak. Four previously published equations that include the variable six-minute walk distance were used to estimate the VO(2)peak: Cahalin, 1996a (1); Cahalin, 1996b (2); Ross, 2010 (3); and Adedoyin, 2010 (4). The agreement between the VO(2)peak in the cardiopulmonary exercise testing and the estimated values was assessed using the Bland–Altman method. A p-value of <0.05 was considered statistically significant. RESULTS: All estimated VO(2)peak values presented moderate correlation (ranging from 0.55 to 0.70; p < 0.001) with measured VO(2)peak values. Equations 2, 3, and 4 underestimated the VO(2)peak by 30%, 15.2%, and 51.2%, respectively, showing significant differences from the actual VO(2)peak measured in the cardiopulmonary exercise testing (p < 0.0001 for all), and the limits of agreement were elevated. The VO(2)peak estimated by equation 1 was similar to that measured by the cardiopulmonary exercise testing, and despite the agreement, bias increased as VO(2)peak increased. CONCLUSIONS: Only equation 1 showed estimated VO(2)peak similar to the measured VO(2)peak; however, a large limits of agreement range (∼3 METs) does not allow its use to estimate maximal VO(2)peak.